The Securitization of Environmental Issues in Southeast Asia - Apriwan Apriwan (Andalas Journal of International Studies (AJIS))
This paper examines how the environmental issues have been securitized in Southeast Asia. It takes three main issues which are atmosphere pollution and deforestation, water resources, and energy resources. The issues could be a potential conflict that will impact to the regional instability. In order to examine the securitization, it uses constructivism approach and securitization concept. This approach and the concept explain about  the response and the action of the states, individual or collective related to that issues. The environmental issues have been emerging conflict among the states which got the impact. For the atmospher pollution and deforestation, Malaysia and Singapore got a tension with Indonesia as the source of problems. On the case of water crisis occured between Malaysia and Singapore in using water resource from Johor, the same cases also happened among the riparian states with China in using the Mekong River Basin. The complicated conflicts about using energy resources have been happening in South China Sea, Thailand’s Gulf and the Ambalat. On the other hand, the state’s response also could make a cooperation among them, which are billateral, multillateral and regional. Thus, securitization of the environmental issues can be seen on how the states give a perception to the issues within an interaction of social structure. Moreover, the states are seen as social actors which interacted within the context of sharing of knowledge, understanding of material resources and the practice of interaction among the states its self.